Suppressing the influence of optical fringes in dispersion spectroscopy - Nikodem, Michal; Wysocki, Gerard (Photonics Letters of Poland, 2013)
In this letter we show that in chirped laser dispersion spectroscopy (CLaDS) a significant reduction of parasitic optical fringes can be achieved. Good agreement between theoretical model and experimental data is demonstrated. Such a fringe reduction capability makes CLaDS technique a good candidate for field applications in which long-term accuracy is critical. Full Text: PDF References A. Cygan et al., "High-signal-to-noise-ratio laser technique for accurate measurements of spectral line parameters", Phys. Rev. A 85, 022508 (2012) CrossRef B. Tuzson et al., "Continuous isotopic composition measurements of tropospheric CO2 at Jungfraujoch (3580 m a.s.l.), Switzerland: real-time observation of regional pollution events", Atmos. Chem. Phys. 11 1685 (2011) CrossRef M. Nikodem, G. Wysocki, "Chirped Laser Dispersion Spectroscopy for Remote Open-Path Trace-Gas Sensing", Sensors 12, 16466 (2012) CrossRef B. Brumfield, et al., "Direct In Situ Quantification of HO2 from a Flow Reactor", J. Phys. Chem. Lett. 4, 872 (2013) CrossRef P. Kluczynski et al., "Detection of acetylene impurities in ethylene and polyethylene manufacturing processes using tunable diode laser spectroscopy in the 3-?m range", Appl. Phys. B 105, 427 (2011) CrossRef M. R. McCurdy et al., "Recent advances of laser-spectroscopy-based techniques for applications in breath analysis", J. Breath Res. 1, 014001 (2007) CrossRef K. Krzempek et al., "CW DFB RT diode laser-based sensor for trace-gas detection of ethane using a novel compact multipass gas absorption cell", Appl. Phys. B 112, 461 (2013) CrossRef R. W. Wood, "The Anomalous Dispersion of Sodium Vapour", Proc. of the Royal Society of London 69, 157 (1902) CrossRef G. C. Bjorklund, "Frequency-modulation spectroscopy: a new method for measuring weak absorptions and dispersions", Opt. Lett. 5, 15 (1980) CrossRef S. Marchett, R. Simili, "Measurement of the refractive index dispersion around an absorbing line", Opt. Comm. 249, 37 (2005) CrossRef R. Lewicki et al., "Ultrasensitive detection of nitric oxide at 5.33 ?m by using external cavity quantum cascade laser-based Faraday rotation spectroscopy", Proc. Natl. Acad. Sci. U. S. A. 106, 12587 (2009) CrossRef P. Ehlers et al., "Fiber-laser-based noise-immune cavity-enhanced optical heterodyne molecular spectrometry instrumentation for Doppler-broadened detection in the 10?12??cm?1?Hz?1/2 region", J. Opt. Soc. Am. B 29, 1305 (2012) CrossRef G. Wysocki, D. Weidmann, "Molecular dispersion spectroscopy for chemical sensing using chirped mid-infrared quantum cascade laser", Opt. Exp. 18, 26123 (2010) CrossRef M. Nikodem, G. Wysocki, "Molecular dispersion spectroscopy ? new capabilities in laser chemical sensing", Ann. NY Acad.Sci. 1260, 101 (2012) CrossRef M. Nikodem, G. Wysocki, "Measuring optically thick molecular samples using chirped laser dispersion spectroscopy", Opt. Lett. 38, 3834 (2013) CrossRef N.-Y. Chou et al., "Optical fringe reduction technique for FM laser spectroscopy", Appl. Opt. 28, 4973 (1989) CrossRef M. Nikodem et al., "Signal-to-noise ratio in chirped laser dispersion spectroscopy", Opt. Expr. 20, 644 (2012) CrossRef A. Fried et al., "Reduction of interference fringes in small multipass absorption cells by pressure modulation", Appl. Opt. 29, 900 (1990) CrossRef